2019
DOI: 10.1007/s00125-019-04973-z
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate increases very-long-chain sphingolipids and improves blood glucose homeostasis in NOD mice

Abstract: Aims/hypothesisSphingolipid metabolism regulates beta cell biology and inflammation and is abnormal at the onset of type 1 diabetes. Fenofibrate, a regulator of sphingolipid metabolism, is known to prevent diabetes in NOD mice. Here, we aimed to investigate the effects of fenofibrate on the pancreatic lipidome, pancreas morphology, pancreatic sympathetic nerves and blood glucose homeostasis in NOD mice.MethodsWe treated female NOD mice with fenofibrate from 3 weeks of age. The pancreatic lipidome was analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Another sphingolipid with a suspected role in T1D pathology is the proapoptotic ceramide of which C16 promotes apoptosis, mitochondrial dysfunction, and insulin resistance [139][140][141][142], while C24 has beneficial roles in regulating metabolic health [141,143]. Recently, we demonstrated that fenofibrate altered ceramide composition in the pancreas of NOD mice increasing C24 and decreasing C16, hence creating a more beneficial ceramide composition [138]. WY14643 was otherwise found to increase ceramide levels in rat hearts [134], suggesting organ-specific regulation 4 PPAR Research of ceramide synthesis.…”
Section: Ppars Regulate Sphingolipid Metabolismmentioning
confidence: 98%
See 1 more Smart Citation
“…Another sphingolipid with a suspected role in T1D pathology is the proapoptotic ceramide of which C16 promotes apoptosis, mitochondrial dysfunction, and insulin resistance [139][140][141][142], while C24 has beneficial roles in regulating metabolic health [141,143]. Recently, we demonstrated that fenofibrate altered ceramide composition in the pancreas of NOD mice increasing C24 and decreasing C16, hence creating a more beneficial ceramide composition [138]. WY14643 was otherwise found to increase ceramide levels in rat hearts [134], suggesting organ-specific regulation 4 PPAR Research of ceramide synthesis.…”
Section: Ppars Regulate Sphingolipid Metabolismmentioning
confidence: 98%
“…PPARα is similarly involved in regulating the composition of sulfatide species with C16 (insulin folding and secretion) and C24 (immune regulation) having different functions [136,137]. In the pancreas, fenofibrate especially increased the amount of C24 sulfatide thereby creating an anti-inflammatory sulfatide composition [138].…”
Section: Ppars Regulate Sphingolipid Metabolismmentioning
confidence: 99%
“…Using fenofibrate, which activates the sulfatide biosynthesis, Holm and colleagues were able to completely prevent diabetes development in NOD mice [14]. In the follow-up study they demonstrated that fenofibrate selectively elevates the pancreatic content of very-long-chain SLs in NOD mice and reduces the incidence of diabetes by around 50% [184]. Moreover they showed that fenofibrate treatment leads to remodeling of pancreatic lipidome with increased amount of lysoglycerophospholipids [184].…”
Section: Animal Modelsmentioning
confidence: 99%
“…In the follow-up study they demonstrated that fenofibrate selectively elevates the pancreatic content of very-long-chain SLs in NOD mice and reduces the incidence of diabetes by around 50% [184]. Moreover they showed that fenofibrate treatment leads to remodeling of pancreatic lipidome with increased amount of lysoglycerophospholipids [184]. NOD mice treated with fenofibrate were characterized by more stable blood glucose and improved glucose tolerance [184].…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation